In vivo modulation of endothelial polarization by Apelin receptor signalling - Kwon, Hyouk-Bum; Wang, Shengpeng; Helker, Christian S. M.; Rasouli, S. Javad; Maischein, Hans-Martin; Offermanns, Stefan; Herzog, Wiebke; Stainier, Didier Y. R. (Nature Communications, 2016)
Endothelial cells (ECs) respond to shear stress by aligning in the direction of flow. However, how ECs respond to flow in complex in vivo environments is less clear. Here we describe an endothelial-specific transgenic zebrafish line, whereby the Golgi apparatus is labelled to allow for in vivo analysis of endothelial polarization. We find that most ECs polarize within 4.5 h after the onset of vigorous blood flow and, by manipulating cardiac function, observe that flow-induced EC polarization is a dynamic and reversible process. Based on its role in EC migration, we analyse the role of Apelin signalling in EC polarization and find that it is critical for this process. Knocking down Apelin receptor function in human primary ECs also affects their polarization. Our study provides new tools to analyse the mechanisms of EC polarization in vivo and reveals an important role in this process for a signalling pathway implicated in cardiovascular disease.
CRIS-Team Scopus Importer:2020-09-23